Early transition to near-zero emissions electricity and carbon dioxide removal is essential to achieve net-zero emissions at a low cost in Australia - Duy Nong; George Verikios; Stuart Whitten; Thomas S. Brinsmead; Daniel Mason-D’Croz; Shelley Rodriguez (Communications Earth & Environment)
Abstract Achieving net-zero emissions requires major changes across a nation’s economy, energy and land systems, particularly due to sectors where emissions are difficult to eliminate. Here we adapt two global scenarios from the International Energy Agency—the net-zero emissions by 2050 and the Stated Policies Scenario—using an integrated numerical economic-energy model tailored to Australia. We explore how emissions may evolve by sector and identify key technologies for decarbonisation. Our results show that a rapid shift to near-zero emissions electricity is central to reducing costs and enabling wider emissions reductions. From 2030 onwards, carbon removal through land management and engineered solutions such as direct air capture and bioenergy with carbon capture and storage becomes critical. Australia is also well-positioned to become a global supplier of clean energy, such as hydrogen made using renewable electricity, helping reduce emissions beyond its borders.